Peruvian helminth fauna: Paryphostomum huaccaci sp. n. (Echinostomotidoe) parásito de Cathartes aura jota Molino, 1782 - Ibáñez H., Nicanor (1974)
It is motive of this present note to contribute to knowledge of one tremotode: Paryphostomum huaccoci sp. n. of the Family Echinostomatidae Poche,1926, parasite of Cathartes aura jota Molina, 1782.